Leveraging blockchain for enhancing electronic data interoperability in Thailand’s port community system: Barriers and strategic enablers - Thoppae, Chaiporn; Supeekit, Tuangyot (Journal of Applied Research on Science and Technology (JARST), 2025)
Thailand’s port logistics sector faces significant challenges in achieving secure and interoperable electronic data exchange across stakeholders. Although a standardized Port Community System (PCS) has been promoted, persistent issues-including fragmented digital platforms, security vulnerabilities, and institutional mistrust-impede Electronic Data Interchange (EDI) effectiveness. This study investigates the key barriers (BAR) to EDI implementation and examines how blockchain technology can be a foundational solution to overcome (OVB) them. A structured survey of 350 PCS service users and providers was administered. The data were examined using Confirmatory Factor Analysis (CFA) to check the different parts of the study and Canonical Correlation Analysis (CCA) to look at the relationships between seven identified barrier factors (like infrastructure, legal issues, and budget) and seven strategies to overcome them (such as technology acceptance, organizational readiness, and management support). The first canonical function showed a strong relationship, with a correlation coefficient of 0.652 (p < 0.01), meaning that certain organizational actions are closely linked to reducing important barriers. This research is the first empirical study in Thailand to apply multivariate statistical modeling to blockchain-enabled PCS adoption. It contributes methodological rigor through validated measurement models, structural analysis, and practical insight for policymakers, port administrators, and logistics managers. The findings suggest blockchain can enhance transparency, trust, and secure data integration in national logistics infrastructures.